PREPARING THE WORKFORCE FOR A 'WAVE OF AGING': FIRST PORT OF CALL IS ADDRESSING SHORTFALLS IN UNIVERSITY CURRICULUM. (11th November 2018) - Scott, T; Kugelman, M
Abstract: The nation needs to prepare to meet the health care needs of a growing older adult population of unprecedented size, and accordingly an exponential growth in numbers of people living with dementia. Despite repeated calls to address increasing need, training an adequate geriatric workforce remains an international concern. This study explored current knowledge, attitudes and biases of an Australian university student sample (n=183), comparing students who would become future health professionals with students in non-health related fields. We measured knowledge of, and attitudes toward dementia and aging, and examined possible diagnostic and prognostic biases through age-manipulation of a hypothetical patient vignette (aged 42 or 72 years). Results showed that while health professional students held significantly different attitudes toward aging than 'other' students, average attitudinal scores indicated neutrality. Health professional students indicated a diagnostic bias toward older vignette patients, who were more likely to be diagnosed with dementia than depression. Attitudes toward patient were affected by age manipulation, such that recommendations were more stereotypically ageist toward the older rather than younger patient - eg. not 'going out alone' and 'wandering off alone'. However, having prior contact with people with dementia predicted more positive prognoses. Overall, the pattern of findings indicated these future Australian health professionals held neutral attitudes towards older people and showed deficits in knowledge of dementia. Introducing students to people living with dementia, through regular guest lectures, may be one achievable way to address curriculum shortfalls, and improve knowledge, skills, and attitudes.